The fauna of the family Adelidae (Insecta, Lepidoptera, Adeloidea) from China - Liao, Cheng-Qing; Hirowatari, Toshiya; Yagi, Sadahisa; Wang, Min; Wang, Xing; Huang, Guo-Hua (Zootaxa, 2023)
Ninety-eight species of the family Adelidae, belonging to three genera in two subfamilies, were recorded and described in China, with illustrations of the adults and their genitalia. Keys to subfamilies, genera and species are also provided. Twenty-four new species are described, nine species are newly recorded from China, and four new combinations are made. Ecological photos and DNA barcodes of some species are provided, and the phylogenetic analysis based on cytochrome c oxidase subunit I (COI) sequences are conducted. The new taxa are as follows: Nemophora pseudalbiantennella Liao, Hirowatari & Huang, sp. nov., N. badagongshana Liao, Hirowatari & Huang, sp. nov., N. longlabiae Liao, Hirowatari & Huang, sp. nov., N. quadrata Liao, Hirowatari & Huang, sp. nov., N. basalistriata Liao, Hirowatari & Huang, sp. nov., N. digitata Liao, Hirowatari & Huang, sp. nov., N. duplicifascia Liao, Hirowatari & Huang, sp. nov., N. hunanensis Liao, Hirowatari & Huang, sp. nov., N. purpurata Liao, Hirowatari & Huang, sp. nov., N. arcuatifasciata Liao, Hirowatari & Huang, sp. nov., N. caeruliantenna Liao, Hirowatari & Huang, sp. nov., N. xizangensis Liao, Hirowatari & Huang, sp. nov., N. caerulea Liao, Hirowatari & Huang, sp. nov., N. songgangensis Liao, Hirowatari & Huang, sp. nov., N. conjugata Liao, Hirowatari & Huang, sp. nov., N. latilobula Liao, Hirowatari & Huang, sp. nov., N. longispina Liao, Hirowatari & Huang, sp. nov., N. ganziensis Liao, Hirowatari & Huang, sp. nov., N. jiajinshana Liao, Hirowatari & Huang, sp. nov., N. litangensis Liao, Hirowatari & Huang, sp. nov., N. tianpingshana Liao, Hirowatari & Huang, sp. nov., N. triangulifascia Liao, Hirowatari & Huang, sp. nov., N. yajiagengensis Liao, Hirowatari & Huang, sp. nov., and N. bispina Liao, Hirowatari & Huang, sp. nov. The newly recorded taxa from China are: Nematopogon distinctus Yasuda, 1957, Adela nobilis Christoph, 1882, A. praepilosa Hirowatari, 1997, Nemophora albiantennella Issiki, 1930, N. chionites (Meyrick, 1907), N. smaragdaspis (Meyrick, 1924), N. trimetrella Stringer, 1930, N. optima (Butler, 1878), and N. bifasciatella Issikii, 1930. The new combinations are N. servata (Meyrick, 1925) com. nov., N. diplophragma (Meyrick, 1938) com. nov., N. chionella (Caradja, 1935) com. nov., and N. chrysocharis (Caradja, 1938) com. nov.